Knowledge, attitudes and behaviour of healthcare workers regarding influenza and vaccination in Salerno, Italy (Italian Journal of Public Health, 2011)
Background: Influenza vaccination coverage among healthcare workers (HCWs) is unacceptably low despitethe recommendations of health authorities.Objective: The aim of the study is to assess the knowledge base of healthcare workers in Local HealthServices (LHS) regarding influenza vaccination and to identify the factors that inhibit or motivate vaccinationamong HCWs.Methods: A cross sectional study was carried out between July and October 2003 within the five Hospitals ofthe LHS “Azienda Sanitaria Salerno2”, Salerno, Italy. In July 2003, we prepared a standardized anonymousquestionnaire for a sample of 280 healthcare workers aimed at surveying their knowledge base and attitudestowards influenza and vaccination. The HCWs were recruited by random selection using the stratifiedlayered sampling method. On the basis of the results of our survey, a hospital vaccination campaign wasundertaken. Statistical analysis was carried out using the EpiInfo 6.06 program. Data were analyzed throughfrequency distribution. Statistical comparison was performed using the Chi-square tests and a p-value
Keywords: influenza; vaccination; healthcare workers; knowledge; attitudes